Optimization for Main Distribution Materials of Low-Voltage Switching Devices (MDU PHBTR) Allocation for Transportation Cost Efficiency in PT PLN (Persero) using Goal Programming - Agus Nugroho, Kusnadi; Siswanto, Nurhadi (Journal Research of Social Science, Economics, and Management, 2026)
Logistics costs for Main Distribution Material (MDU) of Low Voltage Switchgear Devices (PHBTR) increased from IDR 12.5 billion in 2023 to IDR 13.9 billion in 2024, alongside persistent delivery delays beyond the Service Level Agreement (SLA) standards (30 days for Sumatera and Jamali; 45 days for Kalimantan and Sulmapana). In 2023, 172 Detailed Contracts (8.35%) experienced delays, affecting 2,223 units (12.18%), while in 2024, 149 contracts (6.34%) were delayed, impacting 1,448 units (7.17%). The key challenge is developing a distribution allocation model that considers supplier cost differences and Unit Induk demand to improve transportation efficiency and reduce delays. This study applies a quantitative approach using internal secondary data from PT PLN Quarter III 2025, involving 17 suppliers and 22 Unit Induk. The Weighted Goal Programming method is employed to address multi-objective trade-offs between minimizing transportation costs and fulfilling regional demand. Modeling using LINGO software produced an optimal transportation cost of IDR 2,129,998,480 with zero deviation, indicating full demand satisfaction. Compared to the initial allocation cost of IDR 2,704,828,480, the optimized model generated savings of IDR 574,830,000 (approximately 21.25%), particularly for the PL-250-2-LBS, PL-400-2-LBS, and PL-400-4-LBS variants. The proposed model offers a practical decision-making framework to control logistics costs and enhance service reliability..